THE EFFECT OF COMPOSITION OF RED ON WASTE (Allium cepa L.) AND DIRTY BUFFET ON BIOGAS RESULTS - Syafni Nola Putri; Azwir Anhar (Serambi Biologi, 2020)
The onion waste (Allium cepa L.) is an organic material that can be used as bioethanol as the cleanest liquid fuel. Shallot is a beneficial source of fermented products because it has a high sugar content and contains various nutrients such as carbohydrates, proteins, fats and cellulose as the main components of biogas production, but shallot waste has a relatively low C/N. Livestock manure also contains nutrients and contains organic matter which is shown by the average yield of C/N vermicompost from buffalo manure higher than vermicompost from cow manure but statistically shows the C/N ratio of vermicompost from cow manure and buffalo is not significantly different. Red onion and buffalo dung waste can be processed into basic materials with the potential to produce biogas, but now the onion waste and buffalo dung farming is a serious problem in the Lembah Gumanti Subdistrict, Solok Regency because it has not been properly treated as a source of environmental pollution. The research was conducted in December 2018 - January 2019 at the State University of Padang. The purpose of this study was to determine the potential mixture of onion waste (Alium cepa L.) and buffalo dung as biogas producers. With 5 different compositions and treatments A 25% waste red onion saturated with water 75% buffalo dung, B 50% red onion waste saturated with 50% water buffalo dung, C 75% waste onion leaves saturated with 25% water buffalo dung , D of buffalo dung and E of saturated red onion leaf waste from the treatment obtained by the third treatment has the best potential for producing biogas among the four other treatments.   Keywords: Red onion waste (Allium cepa L.), Buffalo dung, biogas.